Serum immunoreactive trypsin concentrations in infectious and non-infectious illnesses and in juvenile diabetes. Issue 9 (September 1979) - Gamble, D R; Moffatt, A; Marks, V
Abstract : Serum immunoreactive trypsin (SIT) concentrations were measured in 244 patients with infectious illnesses and in 281 children with diabetes of recent onset. Results were compared with reference ranges established in 107 patients with non-infectious, non-diabetic illnesses, in whom SIT concentrations were found to increase with advancing age. Reduced or undetectable concentrations of SIT were associated with diabetes in children and with a few cases of severe childhood infection. Increased SIT concentrations were associated with virologically confirmed cases of infection with mumps and Coxsackie B virus infection, and with clinical diagnoses of mumps, PUO, and meningitis in children, and with Bornholm disease, cardiac infection, and respiratory infection in adults. It is suggested that silent invasion of the exocrine pancreas with elevation of the SIT concentration may accompany infection by Coxsackie B, mumps, and, possibly, other viruses.